Financial risk management - Hurley, Brian
Financial risk refers to the possibility of losing money in an investment or in a business venture. This risk can come in a variety of forms including operational risk, credit risk and liquidity risk. Both individuals and organizations can experience these kinds of risks. The practice of assessing and managing potential and current financial risks in order to reduce an organization's exposure to risk is known as financial risk management. It entails recognizing the risk, quantifying it, assessing all viable solutions, formulating a plan and then implementing the steps and financial tools required to mitigate its potential consequences.